Registration of YouTube Content as a Productive Asset from the Istislah Perspective - Khykhy Syorgawi Siregar; Sahliah (Warmadewa Press, 2024)
This study aims to examine the protection and registration of YouTube content as a productive asset through the perspective of istislah in Islamic law. The research method used is a literature review and legal analysis focusing on regulations in Indonesia, including Law Number 28 of 2014 on Copyright, Law Number 6 of 2023 on the Stipulation of Government Regulation in Lieu of Law on Job Creation, and Government Regulation No. 24 of 2022 on the Creative Economy. The results show that YouTube content has great potential to become a valuable asset with strong legal protection. Existing regulations in Indonesia allow YouTube content copyright to be automatically protected and used as fiduciary collateral. The copyright registration process involves several steps ensuring that creators have physical proof of their works, which is crucial for resolving legal disputes. This protection aligns with the principle of istislah in Islamic law, emphasizing public welfare and encouraging innovation and creativity. The conclusion of this study is that legal protection and registration of YouTube content as a productive asset not only protect creators' rights but also promote the growth of the creative economy. With this protection, creators can maximize the value of their content as a source of income and long-term investment. The perspective of istislah provides an ethical and legal foundation to support this policy, ensuring that its benefits are felt by the wider community.